Analisis Arus Lalu Lintas Terhadap Kapasitas dan Tingkat Pelayanan Jalan Tgk. Chik Ditiro Akibat Kegiatan Pembangunan Fly Over Jembatan Simpang Surabaya Banda Aceh - Bunyamin Bunyamin (Jurnal Teknik Sipil Unaya, 2020)
Fly over construction on Tgk. Chik Ditiro Simpang Surabaya street had an impact on increasing loading in some road corridors. The object of this research was to determine the capacity and level of service Tgk. Chik Ditiro street due to the influence of the construction of a fly over and the comparison of traffic flow during and after the construction of the fly over. The method used was MKJI (1997). Retrieval of data for 3 days namely Monday, Wednesday and Friday during and after the construction of fly over, which the West and East side. The highest traffic volume at peak hours in the West Monday morning occurred at 07.00 to 08.00 WIB of 3101.10 (pcu / hour) which decreased of 1357.00 pcu / hour or 69.56%. The highest traffic volume in the East on Monday morning at 07.00 - 08.00 WIB by 3060.00 (pcu / hour) which decreased by 1346.50 pcu / hour or 69.45%. The capacity of the road during and after the construction of the fly over were stable at 2509.83 pcu / hour. The degree of saturation during the fly over construction in the West was 1.24 and the East was 1.22 which means that there were big obstacles. The degree of saturation after the fly over construction was 0.54, which means that the current was stable.